Screening of low-cost materials as heterogeneous catalysts for olive mill wastewater Fenton’s peroxidation - Domingues, Eva F. (2020)
Olive mill wastewater (OMW) is a complex effluent, with a high organic load and toxic compounds. Its seasonal production is an added difficulty for treatment systems. In this work, the heterogeneous Fenton process is used with low-cost catalysts, that are wastes rich in iron and other materials naturally present in nature, namely Red Mud (RM), the volcanic rocks of the Azores (VRA) and the volcanic rocks of the Canaries (VRC), to treat a mixture of five phenolic compounds usually present in OMW (3,4 - Dihydroxybenzoic, 4 - Hydroxybenzoic, 3,4 - Dimethoxybenzoic, 3,4,5 - Trimethoxybenzoic and Trans-cinnamic acids). The effect of adding hydrogen peroxide stepwise was also investigated and it was found that adding the oxidant at once is more efficient than the staged addition, for removing phenols as well as leading to less residual hydrogen peroxide. With regard to the utilization of low-cost catalysts, it was concluded that at the end of 60 min and for a concentration of 1 g/L of catalyst, the removal of phenolic content reaches 100% for RM, while in the case of VRA and VRC this value is 72.0% and 74.6%, respectively.